Noisy chaotic time series forecast approximated by combining Reny's entropy with energy associated to series method: Application to rainfall series - Rodriguez Rivero, Cristian; Pucheta, Julián; Laboret, Sergio; Sauchelli, Victor; Orjuela-Cañon, Alvaro David; Franco, Leonardo (2024)
Fil: Rodriguez Rivero, Cristian. Universidad Nacional de Córdoba. Departamento de Ingeniería Electrónica; Argentina.